Patient Care Management Using A Multi-Agent Approach - SHANKARARAMAN, Venky (Institutional Knowledge at Singapore Management University, 2000)
Patient management and medical decision making involves collaboration between a number of health professionals such as nurses, laboratory analysts, general practitioners, specialist consultants and the patients. This is particularly true for chronic diseases where the follow up takes place over a long period of time involving a number of people. We present our ongoing research effort in the application of multi-agent systems to support patient care management through effective collaboration between health professionals. We present a conceptual model of our approach and then describe a prototype system for diabetic patient care management that has been implemented using the Java Agent Development Environment (JADE)